Sky - Sherman, Ondine (St Ives, NSW : The Author People, 2017)
"Sometimes you have to lose everything to find yourself. After her mother's death, Sky leaves her city life to move in with her aunt and uncle in a small Australian town. But the city isn't all that she leaves behind. Trying to fit in with her new friends means doing things she never dreamt she'd do. Just as she thinks everything is starting to feel normal, Sky stumbles on a case of animal cruelty that forces her to make some tough decisions. Will Sky risk everything to stand up for what she believes in?"--Website.
For ages 12-15.
Keywords: Mothers -- Death -- Juvenile fiction; Aunts -- Juvenile fiction; Teenage girls -- Juvenile fiction; Moving, Household -- Australia -- Juvenile fiction; Country life -- Australia -- Juvenile fiction; Animal welfare -- Australia -- Juvenile fiction; Australian